Structured tool to improve clinical outcomes of type 2 diabetes mellitus patients: A randomized controlled trial - Ayadurai, S.; Sunderland, Bruce; Tee, L.; Md Said, S.; Hattingh, H. (John Wiley and Sons Inc., 2018)
© 2018 Ruijin Hospital, Shanghai Jiaotong University School of Medicine and John Wiley & Sons Australia, Ltd Background: Reviewing pharmacist diabetes intervention studies revealed a lack of structured process in providing diabetes care, leading to varied results from increased to minimal improvements. The aim of this study was to determine the effectiveness of the Simpler tool, a structured clinical guidelines tool, in the delivery of diabetes care. The primary outcome was significant improvement in HbA1c. Secondary outcomes were improved lipid profiles and blood pressure (BP). Methods: A 6-month parallel multicenter two-arm, single-blind randomized controlled trial involving 14 pharmacists at seven primary care clinics was conducted in Johor, Malaysia. Pharmacists without prior specialized diabetes training were trained to use the tool. Patients were randomized within each center to either Simpler care (SC), receiving care from pharmacists who used the tool (n =55), or usual care (UC), receiving usual care and dispensing services (n = 69). Results: Compared with UC, SC significantly reduced HbA1c (mean reduction 1.59% [95% confidence interval CI -2.2, -0.9] vs 0.25% [95% CI -0.62, 0.11], respectively; P = 0.001), and significantly improved systolic BP (-6.28 mmHg [95% CI -10.5, 2.0] vs 0.26 mmHg [95% CI -3.74, 0.43], respectively; P = 0.005). A significantly higher proportion of patients in the SC than UC arm reached the Malaysian guideline treatment goals for HbA1c (14.3% vs 1.5%; P = 0.020), systolic BP (80% vs 42%; P = 0.001), and low-density lipoprotein cholesterol (60.5% vs 40.4%; P = 0.046). Conclusions: Using the Simpler tool facilitated the delivery of comprehensive evidence-based diabetes management and significantly improved clinical outcomes. The Simpler tool supported pharmacists in providing enhanced structured diabetes care.